Inhibition of α-Smooth Muscle Actin Expression and Migration of Pterygium Fibroblasts by Coculture with Amniotic Mesenchymal Stem Cells. (November 2014) - Sha, Xiangyin; Wen, Ye; Liu, Zhiping; Song, Li; Peng, Juan; Xie, Lifei
Abstract Purpose: Epithelial–mesenchymal transition (EMT) of normal conjunctival tissues is a major reason of pterygium generation; α-smooth muscle actin (α-SMA) is a maker in EMT. In this study, we investigated if human amniotic mesenchymal stem cells (hAMSCs) can inhibit α-SMA expression and migration of human pterygium fibroblasts (hPFs) in vitro. Materials and methods: Coculture of hAMSCs and hPFs was completed by using a Transwell coculture system. The α-SMA expression of hPFs was detected by immunocytochemistry and western blot analysis. The migration ability of hPFs was measured by means of a migration assay. Immunoreactivity for α-SMA was detected in all pterygium fibroblasts examined. Results: The expression of α-SMA in cocultured hPFs was significantly lower than in hPFs. Similar result was demonstrated in western blot analysis. In addition, migration assay showed that hAMSCs reduce the migration of hPFs. Conclusions: These results suggested that hAMSCs have the potential to inhibit the generation and invasiveness of pterygium in vitro.